HUBUNGAN PENGETAHUAN ORANGTUA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA KELUARGA DI LINGKUNGAN IV KELURAHAN SEI PUTIH TENGAH MEDAN TAHUN 2013 - erwinsyah putra; alam bakti kaloko; namora lamongga lubis (Lingkungan dan Kesehatan Kerja, 2014)
Health is a human right and as an investment for a successful nation-building. Health development geared to achieving Healthy Indonesia, that is a situation where everyone lives in a healthy environment, healthy and clean living, behaving, have access to health care services and extended health care degrees (Department of health, 2009). This research was conducted to determine the relationship of parental knowledge with Living clean and healthy Behaviors (PHBS) in the neighborhood of White Center neighborhood IV Sei Field by 2013, analytical approach to quantitative in nature. Data collection was done through direct interviews with the questionnaire. The population of this research is the parent totalled 284 people, and a sample of 72 people taken by Accidental Random Sampling. The results showed that most respondents age is 41-50 years 31 people (43,1%), sex women 38 (52,8%), religion was Protestant (72,2%) of 52 people, an ethnic group is a batak 63 people (87,5%), educational ADMIN, last was 43 people (59,7%), self-employed job is 24 people (33,3%), and the monthly income is 2.000.000-3.000.000 33 people (45,8%). Results of statistical tests of correlation chi square can be seen that the variables of parental knowledge about eradicating larva at home with parental behavior variables about eradicating larva at home p = 0,015 (& lt; 0,05), while the results of statistical tests of correlation between the variable square chi parental knowledge about not smoking inside the House with the parental behavior of variables not to smoke inside the home and parental knowledge about variables using clean water with the parental behavior of variables using clean water obtained the value of p = 0,010 (& lt; 0,05) and p = 0,011 (& lt; 0,05), it means there is a very strong relationship. It is recommended also for the environmental community IV in hope more keep their environment again and behave clean living and healthy. Also head of environment IV more actively invites the community to eradicate/clean environment of the mosquito larva. And for public health Rantang more enterprising again held a health promotion in particular the PHBS. Keywords: parental Knowledge, clean and healthy lifestyles